THE INNOVATION THEORY OF JOSEPH SCHUMPETER: FROM THE CLASSICAL DEFINITION OF THE TERM “INNOVATION” UP TO THE MODERN UNDERSTANDING OF THE INNOVATION IDEAS - A. Masliukivska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper studies the evolution of the appearance of the term “innovation” and its classical definition. The study exposes the main provisions of innovation theory of Joseph Schumpeter and their modern understanding.